2016
DOI: 10.1001/jamaoto.2016.0104
|View full text |Cite
|
Sign up to set email alerts
|

A National Perspective of the Risk, Presentation, and Outcomes of Pediatric Thyroid Cancer

Abstract: Compared with thyroid cancer in adults, pediatric thyroid cancer is more likely to present as advanced disease and to be managed by low-volume or pediatric surgeons. In addition, within the United States, surgeon volume appears to be more crucial in determining thyroidectomy outcomes than the surgeon's field of specialization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 22 publications
4
37
0
2
Order By: Relevance
“…2). Compared to adults, PTC in pediatric and adolescents presents more lymph node metastases, distant metastases and recurrence (24, 25). Combining the study mentioned above, the phenomenon that less number of BRAF V600E mutations appears in patients aged under 25 years suggested that aggressive features displayed in these patients may not be caused by BRAF V600E mutation.…”
Section: Discussionmentioning
confidence: 99%
“…2). Compared to adults, PTC in pediatric and adolescents presents more lymph node metastases, distant metastases and recurrence (24, 25). Combining the study mentioned above, the phenomenon that less number of BRAF V600E mutations appears in patients aged under 25 years suggested that aggressive features displayed in these patients may not be caused by BRAF V600E mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Transient hypocalcemia is one of the most common postoperative complications following thyroid surgery in clinical practice. 8 , 9 It has been reported that the rate of postoperative transient hypocalcemia ranges from 6% to 30%, 10 12 although there is ≤2% incidence of persistent dysfunction. The nadir of hypocalcemia often appears within 48 hours after thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Qurayshi et al recently reported, in agreement with prior analyses, 1,2 that children with thyroid cancer, though rare, more commonly present with metastatic and advanced disease and frequently require cervical lymph node dissections. 3 Perhaps as a response to this recognized difference, among others in pediatric thyroid disease presentation, the American Thyroid Association (ATA) recently released management guidelines for children with thyroid nodules and differentiated cancers. 4 These guidelines harbor the potential to influence practitioners whose treatment practices and surgical recommendations previously employed a more conservative approach to pediatric thyroid disease.…”
mentioning
confidence: 99%